2020
DOI: 10.1007/s40194-020-01027-6
|View full text |Cite
|
Sign up to set email alerts
|

Convolution neural network model with improved pooling strategy and feature selection for weld defect recognition

Abstract: Weld defect recognition plays an important role in the manufacturing process of large-scale equipment. Traditional methods generally include several serial steps, such as image preprocessing, region segmentation, feature extraction, and type recognition. The results of each step have significant impact on the accuracy of the final defect identification. The convolutional neural network (CNN) has strong pattern recognition ability, which can overcome the above problem. However, there are two problems: one is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Due to the much larger test set sample size in this study (about 500 on average), the lower 95% confidence bound (dashed line) is close to the POD curves. Considering the patch size (512 × 512 pixels), the material was large in comparison to other weld data sets [23,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the much larger test set sample size in this study (about 500 on average), the lower 95% confidence bound (dashed line) is close to the POD curves. Considering the patch size (512 × 512 pixels), the material was large in comparison to other weld data sets [23,35].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated that this conventional data augmentation has limited scope and additional data augmentation offers diminishing returns. Jiang et al [23] proposed a novel pooling strategy for CNNs to better represent dark and light defects like slag and tungsten inclusion, and classified defects into six categories: crack, lack of fusion, lack of penetration, slag inclusion, porosity and non-defect. They used a set of 3486 32 × 32 pixel images divided into the six categories for training.…”
Section: Automation In Digital Radiography Ndementioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, for example, the article "Unsupervised Pre-Training of Imbalanced Data for Identification of Wafer Map Defect Patterns" written by Shon et al (2021), where the proposed model is based on convolution variational autoencoder (CVAE), achieved a 95.1% level of F-measure. In our analysis, we found out that more than 42% of composed primary studies implementing NN are focused on CNN, for example, Lin et al (2019), Wang et al (2018) 2020), Cerezci et al (2020) or Jiang et al (2021). R-CNN algorithm is also often used (more than 13%), for example, in Tabernik et al (2019), Shi et al (2020a), Liyun et al (2020), Zhao et al (2020a), Zhang & Shen (2021) or Zhao et al (2021).…”
Section: • Neural Networkmentioning
confidence: 99%
“…They have used the deep neural network (DNN) and multilayer bi-directional long short-term memory (BiLSTM) with the attention mechanism to forecast overdue repayment behavior. Jiang et al [17] have proposed an improved feature selection approach by integrating the CNN with the Relief algorithm. Also, Kaddar et al in [7] have used the ANOVA technique to find the non-redundant representation in CNN by obtaining the feature maps with various neuron responses.…”
Section: Literature Reviewmentioning
confidence: 99%